CO2 Capture and Separation by Mono‐Vacancy Doped Graphene in Electric Field: A DFT study. Issue 13 (3rd April 2023) - Wang, Yi; Wang, Huhu; Zhang, Na; Wang, Danqi; Wang, Ruicong; Peng, Wencai; Zhang, Jianshu; Liu, Jichang; Zhang, Jinli
Abstract: In order to reduce the CO2 content of gas pollution, it is necessary to develop more efficient, controllable and sensitive adsorption materials. In this work, the capture of CO2 by 3N‐M‐VG (3N doped mono‐vacancy graphene) nanosheets in the electric field of 0.000–0.040 a. u. were investigated by density functional theory (DFT) simulations. The interaction between CO2 and 3N‐M‐VG increased with increasing applied electric field and the adsorption of CO2 by 3N‐M‐VG underwent a transition from physical to chemisorption at electric field strengths of 0.020–0.030 a. u. In addition, the material allows the capture and release of CO2 by switching on and off an applied electric field. CO2 adsorption and selectivity of 3N‐M‐VG in CH4 /H2 /CO2 gas mixtures can be greatly improved by applying an electric field. Theoretical results of this study can provide guidance for the design of highly selective CO2 capture materials. Abstract : The presence of an applied electric field was found to enhance the adsorption behavior of 3N‐M‐VG nanosheets on CO2 by DFT calculations. And the transition from chemisorption to physisorption was achieved at 0.02–0.03 a. u. Furthermore, the adsorption/desorption behavior of 3N‐M‐VG on CO2 can be achieved by turning on/off the applied electric field.